2013
DOI: 10.1159/000351096
|View full text |Cite
|
Sign up to set email alerts
|

MK886 Reduces Cerebral Amyloid Angiopathy Severity in TgCRND8 Mice

Abstract: Background: Deposition of amyloid-β (Aβ) in blood vessel walls as cerebral amyloid angiopathy (CAA) is observed in the majority of Alzheimer's disease (AD) brains. Inhibition of the 5-lipoxygenase (5-LOX) pathway has recently been suggested to play a role in reducing parenchymal Aβ deposition. However, products of the 5-LOX pathway also activate the peroxisome proliferator-activated receptor (PPAR) family, which promotes clearance of Aβ from the brain. Methods: In the present study, we investigated the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…Aberration in Y-maze exploratory behavior represents impairment in short-term working memory while fear-conditioned memory impairment assesses hippocampal-dependent and hippocampal-independent memory building processes. In line with our data on synaptic integrity and LTP, 5LO inhibition and knockout restored learning and memory impairments in the transgenic mice as assessed by these paradigms to a level indistinguishable from their wild-type controls [15, 17, 32]. Therefore, given this collective data, we have established that 5LO plays a role in improving the behavioral phenotype of AD animal models as well as its biochemical and electrophysiological dysfunctions.…”
Section: Lo and Ad Synaptic Function And Memory Impairmentsupporting
confidence: 85%
See 1 more Smart Citation
“…Aberration in Y-maze exploratory behavior represents impairment in short-term working memory while fear-conditioned memory impairment assesses hippocampal-dependent and hippocampal-independent memory building processes. In line with our data on synaptic integrity and LTP, 5LO inhibition and knockout restored learning and memory impairments in the transgenic mice as assessed by these paradigms to a level indistinguishable from their wild-type controls [15, 17, 32]. Therefore, given this collective data, we have established that 5LO plays a role in improving the behavioral phenotype of AD animal models as well as its biochemical and electrophysiological dysfunctions.…”
Section: Lo and Ad Synaptic Function And Memory Impairmentsupporting
confidence: 85%
“…Thus, we fed Tg2576 animals rodent chow supplemented with the 5LO inhibitor zileuton, from early adulthood, and found as with our knockout studies, that this pharmacologic approach also reduced brain Aβ peptide levels and amyloid plaques burden [16]. Interestingly, a recent paper showed that pharmacologic blockade of 5LO activating protein reduces amyloid angiopathy in TgCRND8 mice and this reduction was associated with a significant decrease in the steady state levels of nicastrin, one of the components of the γ-secretase complex [17]. …”
Section: Lo and Aβmentioning
confidence: 59%
“…The Thioflavin S staining was performed as previously described by Hawkes et al [13]. Briefly, brain sections were deparaffinized and hydrated with the clearing agent xylene and a series of grade ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have suggested that the perivascular accumulation of Aβ damages the BBB, leading to microbleedings, inflammatory reactions, and subsequent damage to the neuronal network (Zlokovic, 2010; Popa-Wagner et al, 2013; Zolezzi and Inestrosa, 2013). On this regard, several authors have demonstrated the role of PPARs as an endothelial protective agents (Zhou et al, 2008; Bae et al, 2010; Kröller-Schön et al, 2013; Zarzuelo et al, 2013; d’Uscio et al, 2014; Hawkes et al, 2014). Recently, it has been demonstrated that PPARs are able to protect endothelial cells from oxidative damage, thus preventing vascular dysfunction, which could favor brain parenchyma alterations (d’Uscio et al, 2012; Papadopoulos et al, 2013).…”
Section: Nuclear Receptors (Nrs): Ppars and Their Potential Role In Amentioning
confidence: 99%
“…Recently, it has been demonstrated that PPARs are able to protect endothelial cells from oxidative damage, thus preventing vascular dysfunction, which could favor brain parenchyma alterations (d’Uscio et al, 2012; Papadopoulos et al, 2013). Based on current knowledge and on our own work, we have proposed that PPAR activation, through natural or synthetic ligands, could protect and recover BBB integrity and functionality by increasing cell antioxidant capacity and improving energy metabolism, leading to the increased expression of specific transporters that could influence the Aβ-clearance rate (Nicolakakis et al, 2008; Zolezzi and Inestrosa, 2013; Zolezzi et al, 2013b; Hawkes et al, 2014). Energy metabolism is vital for both, neurons and the BBB, primarily because the preservation of the ion gradients (in the case of neurons) and the traffic across the BBB requires large amounts of energy (Abbott et al, 2010; Liebner and Plate, 2010; Popa-Wagner et al, 2013).…”
Section: Nuclear Receptors (Nrs): Ppars and Their Potential Role In Amentioning
confidence: 99%